INTEGRASI PERUNDANGAN ZAKAT UNTUK KETAHANAN IKLIM DAN PEMBANGUNAN MAMPAN DI MALAYSIA: Integration of Zakat Legislation for Climate Resilience and Sustainable Development in Malaysia - Arsad, Muhammad Ilhamuddin; Jamaludin, Mohd Hafiz; Samudin, Siti Aisyah (Journal of Shariah Law Research, 2025)
This research explores the integration of zakat into climate resilience strategies in Malaysia, aiming to address the dual challenges of environmental sustainability and socio-economic equity. Climate change poses significant threats to Malaysia such as water scarcity and extreme weather events which disproportionately affect vulnerable communities. This research finds that zakat, has significant untapped potential as a source of money for initiatives to mitigate and adapt to climate change. This research utilizes a library research approach to undertake content and descriptive evaluations of pertinent literature, policy papers and case studies. The results show that zakat can be successfully diverted to environmentally friendly initiatives like sustainable agriculture and water infrastructure which will increase community resilience to the effects of climate change. However, obstacles such as varied legal frameworks, poor public awareness and the necessity for strategic alignment with national objectives impede its complete potential. This research suggests making clear rules for managing zakat, including it in national climate plans and running public education programs to help more people understand how important zakat is for protecting the environment. This holistic approach can transform zakat into a dynamic instrument for achieving climate resilience and a just transition in Malaysia thus promoting both environmental stewardship and social justice.